Anatomical plasticity and starch allocation in an invasive grass in response to fire - Rosalem, Patrícia Fernanda [UNESP]; Gorgone-Barbosa, Elizabeth [UNESP]; de Camargos, Liliane Santos [UNESP]; Martins, Aline Redondo [UNESP] (Springer Nature, 2024)
Investigating the effects caused by different fire frequencies on the tissue thickness of vegetative organs and the concentration of starch reserves of an invasive species in these same organs could elucidate some gaps, or be the first step towards future, further studies. In such a way, the results can contribute to understanding this species resistance mechanisms related to abiotic stress. This study aimed to understand whether fire frequency in invaded areas by Urochloa brizantha (A.Rich.) R.D.Webster caused anatomical and physiological changes in this species. Twelve samples were collected per fire treatment in areas with different event frequencies: fire exclusion, annual and biennial fires. Anatomical, histochemical and physiological analysis were performed on the leaves, rhizomes and roots. Our anatomical results showed that there was an increase in the thickness of the vascular bundle of U. brizantha leaves in the treatment of biennial burning. There were no anatomical differences in the roots. In the rhizomes, epidermis of the burned plants had greater thicknesses, the parenchyma and the vascular bundle of the biennially burned plants were more spherical than in unburned plants and in plants burned annually. These anatomical changes in grass tissues in response to fire have not yet been reported in the literature. In the physiological analyses, we found differences in the starch concentrations, with the different organs, the root presented more than 60% of the starch stored in the entire plant. Fire is changing the anatomy of this species, since there was an increase in the thickness of leaf tissues and also in rhizome tissues. The concentrations of starch in the root guaranteed plant to rapidly resprout after burning, which could be considered an advantage in post-fire environments to occupy rapidly the open spaces.
Keywords: Cerrado; Plant anatomy; Regrowth; Reserves; Urochloa spp